Negation and events as truthmakers - Fernando, Tim (Proceedings of the Amsterdam Colloquium, 2015)
Kit Fine’s conception of truthmakers as exact verifiers and falsifiers provides an approach to negation that can be tested against the notion that events are truthmakers. Temporally locating events presents complications that call for an account of indices at bounded but refinable granularity. A proposal is outlined that links grain with the choice of a finite alphabet, from which strings are formed representing change under forces. Fusing strings is noted to lead to sets of strings, raising the prospects of fusion as a non-deterministic operation against the prospects of truthmakers as string sets.